Plasmid-Mediated mcr-1 Colistin Resistance in Escherichia coli from a Black Kite in Russia - Tarabai, Hassan; Valcek, Adam; Jamborova, Ivana; Vazhov, Sergey V; Karyakin, Igor V; Raab, Rainer; Literak, Ivan; Dolejska, Monika (Antimicrobial agents and chemotherapy, 2019)
The gene mcr-1 conferring resistance to last-line antibiotic colistin has been reported globally. Here, we describe the first detection of plasmid-mediated colistin resistance in Russian wildlife, an isolate of Escherichia coli sequence type 2280 from a black kite (Milvus migrans) scavenging raptor. Whole-genome sequencing and plasmid transferability experiments revealed that mcr-1.1 was located on conjugative IncI2 plasmid pDR164 (59891 bp). Migratory black kites may contribute to the global spread of mobile colistin resistance.
Keywords: Animals; kolistin; Escherichia coli Infections; infekce vyvolané Escherichia coli; Animal Migration; mikrobiální testy citlivosti; Colistin; Escherichia coli; Whole Genome Sequencing; dravci; Anti-Bacterial Agents; proteiny z Escherichia coli; bakteriální léková rezistence; Microbial Sensitivity Tests; plazmidy; sekvenování celého genomu; Russia; Raptors; migrace zvířat; Plasmids; zvířata; antibakteriální látky; Drug Resistance, Bacterial; Escherichia coli Proteins; Rusko